Use of radiographic measurements in the evaluation of dogs with medial patellar luxation - Mortari, Ana C. [UNESP]; Rahal, Sheila Canevese [UNESP]; Vulcano, Luiz Carlos [UNESP]; da Silva, Vicente Colombi [UNESP]; Volpi, Reinaldo S. [UNESP] (Canadian Vet Med Assoc, 2009)
This prospective study used radiographic techniques to evaluate the inclination, Norberg, quadriceps and femoral varus angles, and the patellar position in dogs with developmental medial patellar luxation. The study also compared these measurements pre- and post-operatively to determine how they were affected by surgical procedures. Eighteen dogs with unilateral or bilateral luxation were used, and 4 groups were established according to luxation grade. Except for the quadriceps angle, there was no difference among the groups preoperatively. Significant differences for the quadriceps angle were observed between Grades I and 3, and between Grades 2 and 3. The Norberg and femoral varus angles and the patellar position showed no changes between pre- and postoperative groups. However, measurements of the preoperative quadriceps angle and postoperative inclination angle may be useful for evaluating dogs with grade-3 luxation. Further studies using other imaging techniques are required in dogs with severe grade-4 luxation due to the difficulty in obtaining a good radiographic position.